2011
DOI: 10.1007/s11192-011-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of academic inbreeding on scientific effectiveness

Abstract: In academia, the term ''inbreeding'' refers to a situation wherein PhDs are employed in the very same institution that trained them during their doctoral studies. Academic inbreeding has a negative perception on the account that it damages both scientific effectiveness and productivity. In this article, the effect of inbreeding on scientific effectiveness is investigated through a case study. This problem is addressed by utilizing Hirsch index as a reliable metric of an academic's scientific productivity. Util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 12 publications
1
52
0
8
Order By: Relevance
“…This analysis is complemented by an analysis of whether publishing during PhD studies results in a greater number of citations during the scientist's career. Citations are indicators of research output visibility-arguably, also of research quality-which are found to be correlated with publication counts (Bosquet and Combes 2013;Inanc and Tuncer 2011). It is critical to analyze citations because doing so allows us to measure the effect that publishing during one's PhD studies has on one's career visibility, success, and impact.…”
Section: Methods Assumptions Derived From the Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is complemented by an analysis of whether publishing during PhD studies results in a greater number of citations during the scientist's career. Citations are indicators of research output visibility-arguably, also of research quality-which are found to be correlated with publication counts (Bosquet and Combes 2013;Inanc and Tuncer 2011). It is critical to analyze citations because doing so allows us to measure the effect that publishing during one's PhD studies has on one's career visibility, success, and impact.…”
Section: Methods Assumptions Derived From the Conceptual Frameworkmentioning
confidence: 99%
“…It also does so by using citations as key indicators of research performance (see Inanc and Tuncer 2011). Past publications and citations are known to contribute to successful grant applications (Van den Besselaar and Leydesdorff 2007), which scientists and academics use to produce further knowledge.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…If the total number of all publications was taken into account, the difference was not so impressive, but the early analyses still proved lower productivity levels of inbred faculty members (Eells and Cleveland 1935). In later papers, most researchers (Hargens and Farr 1973;Dutton 1980;Eisenberg and Wells 2000;Horta et al 2007;Inanc and Tuncer 2011;Horta 2013) came to the same conclusions.…”
mentioning
confidence: 98%
“…Other issues such as academic inbreeding. [20] relation between state funding and performance, number and characteristics of doctorate students and their scientific output as well as relation between scholars' gender and salaries and performance could be closely monitored and explored. A useful extension of this work is to incorporate representative international departments in order to better monitor the scientific progress and examine whether it is calibrated to an international level.…”
Section: Resultsmentioning
confidence: 99%